2014
DOI: 10.1007/s00167-014-3321-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tibial rotation on knee medial and lateral compartment contact pressure

Abstract: This experimental study demonstrated that 15° IR of the tibial shaft increased contact pressure and 15° ER decreased contact pressure over the knee medial compartment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
1
20
1
Order By: Relevance
“…Increased forefoot abduction, as found in the FPg, has recently been reported as a predictive factor for lower limb MSD 12,41 . Similarly, higher knee internal rotation (also found in the FPg) has been shown to be a risk factor for the development of MSD of the knee and tibia 7,10,42 . The increased pelvic ROM in the sagittal and transverse planes observed in the FPg could accentuate the lumbar lordosis and increase the risk of low back pain 36,43 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Increased forefoot abduction, as found in the FPg, has recently been reported as a predictive factor for lower limb MSD 12,41 . Similarly, higher knee internal rotation (also found in the FPg) has been shown to be a risk factor for the development of MSD of the knee and tibia 7,10,42 . The increased pelvic ROM in the sagittal and transverse planes observed in the FPg could accentuate the lumbar lordosis and increase the risk of low back pain 36,43 .…”
Section: Discussionmentioning
confidence: 92%
“…12,41 Similarly, higher knee internal rotation (also found in the FPg) has been shown to be a risk factor for the development of MSD of the knee and tibia. 7,10,42 The increased pelvic ROM in the sagittal and transverse planes observed in the FPg could accentuate the lumbar lordosis and increase the risk of low back pain. 36,43 Therefore, although this study did not directly assess the relationship between FP and MSD, it seems reasonable to believe that FP might increase the risk of MSD due to the effects of FP on the whole kinematic chain.…”
Section: Potential Role Of Pronated Foot Function In Msdmentioning
confidence: 99%
“…This may be caused by several factors such as anatomical and biomechanical differences. The mean pressure of the lateral compartment was approximately 60% of that of the medial compartment of the knee . The lateral tibial plateau has a convex shape and load might be supported mainly by articular cartilage.…”
Section: Discussionmentioning
confidence: 97%
“…The clinical implications of the current study are highlighted in a recent biomechanical study by Yazdi et al [22] that investigated the effect of tibial torsion on the contact pressures of the knee joint. That study showed that 15˚of internal rotation of the distal tibia below the osteotomy site increased the medial compartment contact pressure by 18% compared with neutral rotation of the distal tibia.…”
Section: Correlation Coefficient P-valuementioning
confidence: 82%